Directed synthesis and magnetic properties of a hexanuclear ferric cluster. (1st September 2018) - Lengyel, Jeff; Stoian, Sebastian A.; Dalal, Naresh; Shatruk, Michael
Graphical abstract: A hexanuclear Fe(III) complex was synthesized by intentional oxidation of an Fe(II) precursor by AgNO2 . Its crystal structure contains two trinuclear subunits, in which Fe(III) ions are centered by a μ3 -oxo linker. The antiferromagnetic S  = 0 ground state of the complex was established experimentally and justified by DFT calculations. Abstract: The hexanuclear iron(III) complex, [Fe6 (µ3 -3-bpp)4 (µ3 -O)2 (µ2 -OMe)3.67 (µ2 -OH)0.33 Cl2 ]·0.33MeOH·H2 O (1 ) was synthesized by a redox reaction between FeCl2, AgNO2, and 3-H2 bpp in methanol (3-H2 bpp = 2, 6-bis(3-pyrazolyl)pyridine). The crystal structure of the complex is composed of two trinuclear subunits related by an inversion operation. This symmetry results in an overall octahedral arrangement of Fe(III) sites within the cluster. The four equatorial Fe sites are linked together by µ2 -OMe − and µ2 -OH − bridges, while each of the four 3-bpp 2− bridges spans two axial and one equatorial Fe sites. The two Cl − ligands cap the axial Fe sites. The difference in the coordination environment for the equatorial and axial Fe sites is validated by the observation of two quadrupole doublets in the Mössbauer spectrum of 1, which also confirms that all metal sites correspond to the high-spin Fe(III) ions. Temperature-dependent magnetic susceptibility data reveal strong antiferromagnetic exchange coupling between the Fe(III) centers, which is also justified by quantum-chemical calculations at the density-functional level of theory.